Pengembangan Atraksi Wisata di Desa Wisata Cibodas Berbasis Masyarakat Kabupaten Bandung - Afriza, Lia; Muttaqien, Raden Rizki; Putra, Widi Widya (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2025)
The development of villages into tourist destinations has become a current trend in regional development programs, as it is considered capable of improving community welfare by increasing the Human Development Index (HDI). By transforming villages into tourism destinations, communities gain opportunities to develop businesses based on local potential, such as managing traditional food and beverages, agricultural activities, and handicrafts that can serve as tourist attractions. In Cibodas Village, natural assets such as rice fields and plantations, along with activities like making satay sticks, banana chips, and bonsai cultivation, serve as important foundations for tourism village development. In addition to driving economic growth, rural tourism also contributes to environmental and cultural preservation. The development model for community-based tourism attractions is implemented in three phases: beginning, middle, and advanced, with the aim of shifting from a directive to a non-directive approach. The directive approach instills a tourism culture through direct guidance, while the non-directive approach reflects a tourism culture that has been internalized within the community’s daily life. Both approaches emphasize the importance of active community involvement in every stage of rural tourism development, ensuring the sustainability and optimal utilization of local potential.